Pengelolaan Retribusi Sektor Pariwisata Dalam Meningkatkan Pendapatan Asli Daerah Kabupaten Takalar - Putra, Rusfadana Dwi; Madani, Muhlis; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to determine the Management of Tourism Sector Levies in Increasing the Original Revenue of Takalar Regency. The type of research used descriptive qualitative. There were 10 informants used in this study .data collection techniques were observation, interview and documentation . Data analysis used the analysis process which was carried out simultaneously with the data collection process. And used 3 types of triangulation in data validation. The results showed that the management of the tourism sector levies in increasing local original income showed quite good , this was seen from the indicators (1) Planning was optimal enough to carry out development and management so that the development of tourism could develop sustainably, (2) Organizing was quite well by dividing positions according to their skills and abilities (3) Directing sufficiently maximally by trying to make planning a reality through various directions (4) Supervision that had been carried out according to management functions.